Whole genome diversity of indigenous chicken populations in Ethiopia - Kebede, A.; Tesfaye, K.; Belay. G.; Vallejo, A.; Dessie, Tadelle; Spark, N.; Hanotte, Olivier H.; Raman, L..; Gheyas, Almas A. (2019)
Indigenous chicken makes most of the world’s poultry genetic diversity particularly in developing countries. These local breeds, which are well- adapted to extensive husbandry systems and suitable for resource-poor poultry farmers endowed with very limited means, should be thoroughly studied as a basis for enhancing their use and conservation. Understanding the link between genomic diversity and adaptability is opening the door to marker-assisted breed improvement programs. Here, we report the genomic diversity of Ethiopian indigenous chicken through discovery and characterization of 21 million SNPs (72% novel) from 27 indigenous chicken populations (n = 260 birds) using whole genome sequencing. In each population around 10 to12 million SNPs are present, of which, 40 - 47% are heterozygote. The mean SNP density for all population across all autosomes is 20 ± 5 per kb. It much lower, for he Z chromosome (mean = 21) and the W chromosomes (mean = 0.4). Principal component and admixture analyses suggest the presence of four ancestral gene pools across the populations. Over 46% of the SNPs are located within genes, of which exonic and intronic SNPs account for 1.59% and 43.94%, respectively; while 31% of the exonic SNPs are non-synonymous. A large proportion of SNPs has low alternative allele frequency (AAF < 10%), although this proportion is higher in exon for potentially harmful categories like missense and stop gain/loss (> 60%) compared to neutral genes (40-45%). Genes with deleterious missense variants are included within several important biological pathways including innate immunity. This study confirms the existence of significant genomic diversity in indigenous chicken populations of Ethiopia, with most of the variants previously undescribed in commercial breeds.